Patterns of Management of Patients With Dual Disorder (Psychosis) in Italy: A Survey of Psychiatrists and Other Physicians Focusing on Clinical Practice - Clerici, Massimo; de Bartolomeis, Andrea; De Filippis, Sergio; Ducci, Giuseppe; Maremmani, Icro; Martinotti, Giovanni; Schifano, Fabrizio (Frontiers in Psychiatry, 2018)
Patients with severe psychotic disorders such as schizophrenia, schizoaffective and bipolar disorders frequently suffer from concomitant substance use disorders (SUDs) – Dual Disorder (DD) patients. In order to better understand current practices for management of patients with psychotic episodes and concomitant SUD in Italy, we carried out a survey of psychiatrists on current routine practice among prescribers. These aspects can help to identify at-risk patients, improve current prescribing practices, and favor early intervention. An ad hoc survey of 17 questions was administered to psychiatrists via electronic polling and on-line distribution; 448 completed questionnaires were collected. Comorbid substance abuse was most frequently diagnosed within the context of anxiety disorder (46%), followed by bipolar disorder (25%), and schizophrenia/schizoaffective disorder (12%). The vast majority of respondents felt that patient management was becoming more complex due to substance abuse. The areas reported to be most affected in patients with SUD were functioning, interpersonal relations, and impulsivity, while sensory perception disorders, ideation, agitation, and impulsivity were the most frequently reported symptoms. In the acute setting, haloperidol was used as the first-line agent of choice followed by aripiprazole and olanzapine. In the maintenance phase, aripiprazole was the dominantly used first-line agent, followed by olanzapine. Almost half of respondents used long-acting agents, while about one-third did not. Among those prescribing long-acting agents, efficacy, control of impulsivity, and control of specific symptoms were cited as motivators, while in the maintenance phase, better adherence and tolerability were mainly cited. From the responses to the present survey, it is clear that the respondents are aware of the problem of SUD in psychotic patients. While treatment be optimized in terms of the choice and formulation of antipsychotics, greater emphasis should be placed on efficacy, tolerability and the negative metabolic consequences of some antipsychotics. When considering the ideal antipsychotic, long-acting agents were considered to be superior in reducing relapse, even if current treatment guidelines often give preference to oral formulations.